Decolonizing climate change response: African indigenous knowledge and sustainable development - David, James Ojochenemi (Frontiers in Sociology, 2024)
BackgroundAnthropogenic Global Warming (AGW) poses a critical challenge necessitating effective global climate change mitigation efforts. However, the pervasive influence of scientism in AGW discourse often marginalizes Indigenous perspectives crucial for addressing climate impacts, particularly in Africa where adaptive capacity is limited.ObjectiveThis study, rooted in Transformative Learning Theory and Ubuntu philosophy, employs critical qualitative research methods to examine how scientism shapes AGW discourse epistemologically and ethically. It explores the hindrances posed by climate change denialism and ecomodernism due to scientism while advocating the integration of African Indigenous Knowledge Systems (AIKs) into climate response strategies, particularly within the African education landscape.MethodsDrawing on the theoretical frameworks of Transformative Learning and Ubuntu philosophy, and informed by critical qualitative research methodology, this research analyzes the role of scientism in AGW discourse. It investigates its implications for Education for Sustainable Development (ESD) and discusses arguments for the inclusion of AIK in educational and policy frameworks.ResultsThe study reveals that scientism perpetuates epistemological biases that undervalue AIK, thereby impeding comprehensive climate response strategies. Pathways are proposed that promote AIK integration and mainstreaming, thereby decolonizing climate response efforts and enhancing ESD within Africa’s educational institutions.ConclusionIntegrating insights from AIK, construed in terms of ‘exemplary ethical communities’ (EEC), into climate change responses is pivotal for fostering inclusive and effective strategies. This approach not only addresses the ethical imperatives of decolonization but also enhances resilience and sustainability in climate-vulnerable regions.SignificanceThis study contributes to scholarship by highlighting the urgent need to diversify climate response strategies through the inclusion of AIK. By advocating for the integration of wisdom from EECs, it advances discussions on decoloniality within climate change discourse, emphasizing the importance of Indigenous knowledge in global sustainability efforts.